Anthropometric Assessment of Nutritional Status of Bangladeshi Pregnant Women and Weight of their Newborns - Momen, Md. Abdul; Yusuf, Harun KM; Alam, Md. Rafiqul (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15281 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.101-105